Feed intake, growth performance and nutrient digestibility in growing Red Sokoto bucks fed supplements containing graded levels of Piliostigma reticulatum pods in semi-arid Nigeria - Abdurrahaman, S. L.; Muhammad, I. R.; Maigandi, S. A. (Nigerian Journal of Animal Science, 2023)
Twenty growing Red Sokoto bucks with average weight of 15.25+0.35kg were used to evaluate the effect of supplementing Piliostigma reticulatum pods (PRP) based diets on feed intake, growth performance and nutrients digestibility. The study was conducted at Teaching and Research Farm, Federal University Dutse. The bucks were randomly assigned to five dietary treatments in a completely randomized design (CRD) and were replicated four times each. The five diets were formulated with 0%, 7.5%, 15%, 22.5% and 30% inclusion levels of PRP for T1, T2, T3, T4 and T5 respectively. The diets were supplemented to the experiment bucks at 2% of their body weight for 84 days; crushed sorghum stalk was used as basal diet. The basal diet and water were provided ad libitum. Data were generated on feed intake, liveweight changes; feed conversion ratio and nutrients digestibility. The results obtained revealed significant differences (P<0.05) in treatments evaluated. Treatment with 0%, 7.5% and 15% PRP inclusion were statistically the same in terms of total feed intake, weight gain and feed conversion ratio compare to others. Daily intake of supplements increases with inclusion level up to T3 (7.5% PRP) and decline thereafter. Treatment with 7.5% PRP (T3) was superior (P<0.05) in digestibility of Ash (47.00%); OM (55.81%) and CP (70.49%) while treatment with 30% PRP inclusion leads in CF (45.33%), EE (34.37%) and NDF (40.53%). This study therefore recommends the inclusion of up to 7.5% of Piliostigma reticulatum pods as feedstuff in ration formulation to serve as supplements to avert dry season feed scarcity.